Research trends in entrepreneurship in the digital era: A bibliometric analysis - Irianto, Okto; Adiatma, Tini; Bagu, Agustin (Privietlab, 2024)
In the digital era, entrepreneurs have begun to leverage ICT and its social capital to overcome obstacles and grow their firms. The idea that digital technology can help address the issues faced by sustainable businesses has gained traction in recent studies. To develop research related to entrepreneurship in the digital era and the potential for new research on this topic. This research used descriptive analysis methods for journal articles indexed in Scopus and Google Scholar. This study investigates the literature using bibliometric analysis methods in five stages: data collection, keyword selection, matrix calculation, result visualization, and data interpretation and visualization results. According to the bibliometric analysis, there were 11 clusters, 161 items, and 447 links with a link strength of 500. Furthermore, according to Scopus and Google Scholar data, most studies on entrepreneurship in the digital era are related to the business environment, pandemics, digital entrepreneurs, digital entrepreneurship ecosystems, digital media, existence, financial literacy, and financial technology. In conclusion, during 2018-2023, there is an increasing trend in digital-era research subjects. Bibliometric analysis, though comprehensive in identifying clusters and connections, may not capture the qualitative nuances and deeper insights within individual studies. This study contributes significantly by mapping the evolving digital entrepreneurship research from to 2018-2023. Through a comprehensive bibliometric analysis, it identifies key research clusters and trends, providing valuable insights for academics, policymakers, and practitioners. The findings illuminate the interconnections between the business environment, pandemic impacts, and technological advancements in digital entrepreneurship.